2015
DOI: 10.1590/s0102-86502015001000010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamine supplementation on left colon healing in rats with extrahepatic biliary obstruction

Abstract: Intellectual and scientific content of the study, designed the protocol, provided guidelines for the surgical interventions, supervised all phases of the study, manuscript writing, critical revision. ABSTRACT PURPOSE:To evaluate the influence of glutamine and obstructive jaundice on left colon healing in rats. METHODS:Sixteen male rats were allocated across four groups: LG -Common bile duct ligation followed by colotomy and bowel suture on postoperative day 7. Supplementation with glutamine 2% from day 4 after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…An additional study demonstrated a subjective trend toward less edema and lower neutrophil cell counts as well as less bacterial colonization and abscess formation in a rat colotomy model. Although subjective improvements were reported, burst strength was not different between glutamine-supplemented and control animals (39). Most of the benefits of supplemental glutamine appear to involve improved gut permeability and protein synthesis, normalization of serum levels, and decreased length of hospital stay (40).…”
Section: Clinical and Preclinical Data Examining Nutrient Supplementamentioning
confidence: 86%
“…An additional study demonstrated a subjective trend toward less edema and lower neutrophil cell counts as well as less bacterial colonization and abscess formation in a rat colotomy model. Although subjective improvements were reported, burst strength was not different between glutamine-supplemented and control animals (39). Most of the benefits of supplemental glutamine appear to involve improved gut permeability and protein synthesis, normalization of serum levels, and decreased length of hospital stay (40).…”
Section: Clinical and Preclinical Data Examining Nutrient Supplementamentioning
confidence: 86%